2016
DOI: 10.1097/olq.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Specific Concordance of Chlamydia trachomatis Genital Infection Within Heterosexual Partnerships

Abstract: Background Sexual transmission rates of Chlamydia trachomatis (Ct) cannot be measured directly; however, the study of concordance of Ct infection in sexual partnerships (dyads) can help to illuminate factors influencing Ct transmission. Methods Heterosexual men and women with Ct infection and their sex partners were enrolled and partner-specific coital and behavioral data collected for the prior 30 days. Microbiological data included Ct culture, nucleic acid amplification testing (NAAT), quantitative Ct poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…Regarding the percentages of concordance, they were lower than those reported by -Infante et al, 2005;Quinn et al, 1996;Schillinger et al, 2016;Tait & Hart, 2002).…”
Section: Discussioncontrasting
confidence: 65%
“…Regarding the percentages of concordance, they were lower than those reported by -Infante et al, 2005;Quinn et al, 1996;Schillinger et al, 2016;Tait & Hart, 2002).…”
Section: Discussioncontrasting
confidence: 65%
“…Obviously, in every partnership at least one of the partners must have had sexual contact with a third party who had a chlamydia infection, but we are not able to determine in how many partnerships both partners separately acquired chlamydia from a third party, as this would require testing all third parties for chlamydia and conducting a molecular analysis of chlamydia serovars. A recently-published study of chlamydia concordance in heterosexual partnerships found that in 96.2% (51/53) of chlamydia-concordant partnerships both partners had the same chlamydia genotype (Schillinger et al, [22]). This finding suggests that concordance represents transmission within partnerships, but as described above, we may not be able to extrapolate from heterosexual partnerships to same sex male partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission rate increased to 70% (53/76) when nucleic acid methods were used for diagnosis. In a study by Schillinger et al (31), based on culture results, ϳ80% concordance between female and male sexual partners was found. Rank et al (26) infected the meatus urethra of male guinea pigs with 10 7 IFU of C. caviae and caged them with naive females.…”
Section: Discussionmentioning
confidence: 94%
“…This mouse model bears similarities with horizontal human sexually transmitted C. trachomatis infections. Two concordant studies reported ϳ70 to 80% transmission rates in females from C. trachomatis-positive males (30,31). For example, Quinn et al (30) studied 494 sexual partner couples using urethral and endocervical swabs for the detection of C. trachomatis.…”
Section: Discussionmentioning
confidence: 99%